ANALISIS KANDUNGAN Pb PADA AIR SUMUR GALI MASYARAKAT DI SEKITAR TEMPAT PENIMBUNAN LIMBAH PADAT INDUSTRI TIMAH DARI DAUR ULANG AKI BEKAS DESA SEI ROTAN KECAMATAN SEI TUAN KABUPATEN DELI SERDANG TAHUN 2012 - Winni R.E Tumanggor; Surya Dharma; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
Analysis of lead containing in the dug wells’ water of communities around of the solid waste dumping of lead insdustry from battery recycling. Dug wells were the most common means used by the people as a major source of clean water. The groundwater quality degradation is characterized by the presence of some pollutants such as lead that can be derived from leaching of hazardous materials, such as ex-storage batteries and ex-inner batteries. The design was descriptive research. It described that the dug well’s construction, lead containing in the water of dug well and the condition of solid waste dumping of lead industry from battery recycling. The samples of dug wells water were taken from 5 spots distance from waste dumping location, they were 25 metres, 50 metres, 100 metres, 150 metres, and 200 metres. Each spots was choosen 2 dug wells so that totals samples are 10. This research had done in Sei Rotan Village Percut Sei Tuan District Deli Serdang Regency 2012. The result of the research showed that none were met with health requirements. The results of the laboratory examination found the all of dug well water samples that lead containing exceed the quality standards established by the Decree of Permenkes No. 416 / Minister / Per / IX / 1990 figure of 0.05 mg / L. It is recommended that, the participation of community and role of government was needed to improve public knowledge about the pollution of lead industry from battery recycling and the physical construction of dug well through training, extension and renovation of the water supply facilities in order to obtain clean water that meets health requirements. Key words : Dug Well Water, Lead Containing